The Mechanisms of Deconstructive practices in Abstract Expressionist Paintigs - حمدان شذى سامي (Basrah Arts Journal, 2025)
Abstract : Keywords: subversion, Derrida, Heidegger, trace, contemporary painting The research dealt with (the mechanism of subversive works in contemporary Iraqi painting) and according to what the contemporary artistic trends produced in terms of a transformation in ideas and a subversion in concepts and techniques as a result of scientific and technological development and intellectual and philosophical transformation, the researcher tried to identify the mechanism o The third chapter included the procedures that the researcher took to reach the research objective, starting with collecting the research community, through selecting the research sample, and arriving at analyzing the sample models. After that, the researcher presented the research results in the fourth chapter, then presented the conclusions, recommendations, and proposals, and finally the index of sources, appendices, and a summary of the research in the English language. subversive works in contemporary Iraqi painting by answering the following question: _ What is the impact of subversive works on contemporary Iraqi painting